The Islamicity of Sharia Rural Banks in Indonesia - Pertiwi, Imanda Firmantyas Putri; Puspitosari, Indriyana; Wijayati, Fitri Laela (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2019)
AbstractThis paper is aimed to evaluate the Islamic Performance of Sharia Rural Banks (SRBs) in Indonesia by using the Islamicity Performance Index (IPI). The data are taken from SRBs from 2014 to 2016 (those include PF and Profit), as well the liquidation of SRBs in those years. The sample is taken by using a purposive sampling technique. Then, there are 82 SRBs samples and observing 246 pcs data. The data are obtained by evaluating their financial reports through the websites of Central Bank of Indonesia or Financial Services Authority (Otoritas Jasa Keuangan-OJK) as well as the SRBs websites. The data are analyzed by non-statistic quantitative and descriptive qualitative techniques. The results are gained from each indicator of their average Islamic Performance Index. The result shows that the Islamic Performance Index of Sharia Rural Banks is unsatisfied. Henceforth, this study has several limitations that may be observed in the next research. Moreover, this research excludes the welfare indicators of the director-employee and AAOIFI index.Penelitian ini bertujuan untuk menilai kinerja keislaman (Islamicity) Bank Perkreditan Rakyat Syariah (BPRS) di Indonesia. Penelitian ini menggunakan sampel BPRS di Indonesia dari tahun 2014 hingga 2016, dengan menggunakan teknik purposive sampling. Sampel akhir yang diperoleh adalah 82 SRB sehingga data yang diamati adalah 246 pcs data. Data diperoleh dengan mengakses laporan keuangan mereka melalui situs web Bank Sentral Indonesia atau Otoritas Jasa Keuangan (OJK) serta situs web masing-masing BPRS. Penelitian ini dianalisa dengan menggunakan teknik kuantitatif non-statistik dan deskriptif kualitatif. Hasil penelitian menemukan bahwa kinerja bank syariah berdasarkan Indeks kinerja keislaman adalah â€œtidak memuaskanâ€. Bagaimanapun, penelitian ini memiliki beberapa batasan yang dapat diperoleh melalui penelitian selanjutnya. Penelitian ini tidak termasuk indikator kesejahteraan direktur-karyawan dan indeks AAOIFI.Â